A new species of Dryopteris (Dryopteridaceae) from China - Lı, Xıaojuan; Zhang, Meılıng; Lı, Jıanxıu (Bangladesh Journal of Botany, 2025)
A new species of Dryopteris songyinghuensis was reported in the study. It is closer to D. peninsulae Kitag. for its morphological and palynological characters of LM and SEM studies but differs by a number of characters, such as, stipe base densely covered with dark-brown, margin dentate lanceolate scales, margin dentate oval scales above middle stipe, rachis and costae with dark brown, margin dentate oval and lanceolate scales, leaves triangular oblong, lower pair of pinnae slightly longer, upward pair of pinnae gradually shortened, bipinnatifid or tripinnatifid, sori spread abaxially, each pinna is lined on either side of the midvein, occurs between the midvein and the margin, perispore with curved strip ridge, semi-ring ornamentation. The sp. nov. is described with LM and SEM characters of spore and fronds, compared with that of D. peninsulae Kitag. and provided with photographs. Bangladesh J. Bot. 54(3): 755-760, 2025 (September) Special